Mesenchymal Stem Cell Therapy and Simvastatin Treatment in Experimental Ischemic Stroke: An Evaluation for Anatomical Repair and Community-Based Stroke Rehabilitation - Ata Ur Rehman1, Kiran Khan, Syed Zaryab Ahmed, Faraz Saleem, Suhail Iqbal, Nausheen Hameed Siddiqui, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Ischemic stroke remains a leading cause of disability, particularly in low- and middle-income countries, where community-based rehabilitation (CBSR) faces resource constraints. Mesenchymal stem cell (MSC) therapy promotes neuroprotection and repair, while simvastatin offers pleiotropic benefits including enhanced cell homing and anti-inflammation. This preclinical study evaluated their combination in a rat MCAO model to assess implications for CBSR. Methods: Sixty adult male Sprague-Dawley rats underwent 90-min transient MCAO and were randomized into five groups (n=12): sham, MCAO vehicle, MCAO + simvastatin (10 mg/kg IP daily ×7 days), MCAO + MSCs (1×10^6 IV at 24h), and combination. Bone marrow MSCs were isolated, characterized (CD90+/CD29+), and administered via tail vein. Outcomes at days 1-28 included Bederson score, adhesive removal/rotarod tests, infarct volume (TTC/Nissl), immunohistochemistry (NeuN/GFAP/CD31/BrdU), western blot (BDNF/VEGF), and qRT-PCR (SDF-1). Data analyzed by ANOVA/Tukey (p<0.05). Results: Combination therapy reduced infarct volume by 62% (12.4±2.8% vs. 32.6±4.1% MCAO, p<0.001), preserved NeuN+ neurons 2.8-fold (145±18/mm²), curbed gliosis 48%, and boosted CD31+ vessels 2.1-fold versus MCAO. Behavioral recovery excelled: Bederson 1.2±0.4 (vs. 3.8±0.7), rotarod 152±22s (vs. 45±12s), adhesive 12.3±3.1s (vs. 35.4±5.6s; all p<0.001), surpassing monotherapies by 30-40%. BDNF/VEGF rose 3.2/2.7-fold, SDF-1 mRNA 4.1-fold. Conclusions: Simvastatin-MSC synergy enhances neuroprotection, angiogenesis, and functional recovery beyond monotherapies, with accessible pharmacology ideal for LMIC CBSR integration. These findings support Phase I translation for scalable stroke rehab. Keywords: Mesenchymal Stem Cells, Simvastatin, Ischemic Stroke, Community Based Stroke, Rehabilitation